REST/NRSF is a master negative transcriptional factor for neurogenic program by maintaining stem cell quiescence in adult hippocampal neurogenesis - Abdelhamid, Mostafa Nashaat Ahmed (AUC Knowledge Fountain, 2011)
Adult neurogenesis occurs in two distinct regions inside the brain, the subventricular zone (SVZ) in the lateral ventricle and the subgranular zone (SGZ) of the dentate gyrus in hippocampus. Neural stem cells (NSCs) are controlled by several intrinsic and extrinsic factors that regulate their proliferation, survival and differentiation in the adult hippocampus. REST/NRSF is considered a master transcription factor that regulates hundreds of neuronal genes essential for neuronal fate decision. In this study, we address the role of REST/NRSF (RE1 silencing transcription factor/Neuro-restrictive silencer factor) in regulating adult neurogenesis in hippocampus.REST/NRSF has biphasic expression in neural stem cells and mature neurons. It serves as a critical controller of neural stem cell fate transition and neuronal differentiation.REST/NRSF maintains neural stem cell quiescence preventing its precocious differentiation into neurons. This study shows that deregulation of REST/NRSF function, conditional deletion in REST/NRSF allele, in vivo leads to a transient increase in adult hippocampal neurogenesis and NSCs exit quiescence. Consequently, this reflects a decrease in newborn neurons due to stem cell pool exhaustion. Our work asserts on the critical role of REST/NRSF as a negative master regulator for adult neurogenesis. The results offer a new horizon for the role of NRSF in regenerative medicine and development of new treatment strategies for cancer research.